Patient family advisors' perspectives on engagement in health‐care quality improvement initiatives: Power and partnership. (28th September 2017) - Goodridge, Donna; Isinger, Tanner; Rotter, Thomas
Abstract: Background: Engagement of the public in defining and shaping the organization and delivery of health care is increasingly viewed as integral to improving quality and promoting transparent decision making. Meaningful engagement of the public in health‐care reform is predicated on shifting entrenched power imbalances between health‐care systems and those it claims to serve. Objectives: To describe the expressions, forms and spaces of power from the perspectives of persons who participated as Patient/Family Advisors (PFAs) in Rapid Process Improvement Workshops (RPIWs) within Saskatchewan, Canada. Methods: Using a qualitative, interpretive approach, in‐depth interviews were conducted with a purposive sample of 18 PFAs who had participated in at least one RPIW over the past year. Deductive thematic analysis was informed by Gaventa's model of power. Results: Motivations for serving as a PFA included a sense of obligation to contribute to the improvement of a public system, recognition of their rights as citizens within a publicly funded system and an opportunity to openly express their concerns where previous encounters had been very negative. The invited spaces of the RPIWs were created by policymakers to accord visible power to PFAs. Participation resulted in PFAs gaining new insights into the structure and operations of the system, affirmation of their right to advocate and recognition of the potential to claim spaces of power as consumers. Advisement on specific health‐care initiatives using the vehicle of PFAs shaped and promoted new forms and spaces of power, representing one step in a very long road to full engagement of consumers in health care.